2021
DOI: 10.1007/s10646-021-02400-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of nontarget organism Chironomus sancticaroli to study the toxic effects of nanoatrazine

Abstract: Atrazine was banned by the European Union in 2004, but is still used in many countries. Agricultural research employing nanotechnology has been developed in order to reduce the impacts to the environment and nontarget organisms. Nanoatrazine was developed as a carrier system and have been considered efficient in weed control. However, its toxicity must be verified with nontarget organisms. In this context, the aim of the present study was to investigate ecotoxicological effects of solid lipid nanoparticles (em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 122 publications
(118 reference statements)
1
5
0
1
Order By: Relevance
“…Moreover, the nanoparticles loaded with atrazine showed similar toxicity to free atrazine which led to mortality and biochemical changes in Chironomus larvae. 80 Similarly, in the present study, NLC–TBZ showed similar toxicity to free TBZ (Fig. 3B and Table 3) on the survival of D. magna .…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…Moreover, the nanoparticles loaded with atrazine showed similar toxicity to free atrazine which led to mortality and biochemical changes in Chironomus larvae. 80 Similarly, in the present study, NLC–TBZ showed similar toxicity to free TBZ (Fig. 3B and Table 3) on the survival of D. magna .…”
Section: Resultssupporting
confidence: 85%
“…It might be possible that lipid-based nanopesticides do not significantly alter the toxicity of the a.s. Albuquerque et al (2021) 80 tested solid lipid nanoparticles loaded with atrazine on the non-target organism, Chironomus sancticaroli , and they reported lethal effects at 2 μg L −1 atrazine (as an environmentally relevant concentration). Moreover, the nanoparticles loaded with atrazine showed similar toxicity to free atrazine which led to mortality and biochemical changes in Chironomus larvae.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Larvas de Chironomussp. são comumente observadas de ambientes eutróficos a ambientes oligotróficos, sendo re- O invertebrado bentônico de água doce C. sancticaroli vem sendo utilizado amplamente como organismo-teste em ensaios ecotoxicológicos nos últimos anos (MORAIS et al, 2014;RICHARDI et al, 2015;PALACIO-CORTÉS et al, 2017;BERNEGOSSI et al, 2019;PINTO et al, 2021b;ALBUQUERQUE et al, 2021). A seleção desse organismo se justifica, entre outras razões, pela sensibilidade e número de respostas expressas ao ser exposto a contaminantes ou amostras ambientais, como perda de variabilidade genética (COLOMBO-CORBI et al, 2017), alteração na atividade enzimática (REBECHI-BAGGIO et al, 2016) ou redução da fecundidade potencial medida pelo comprimento das asas (TRIVINHO-STRIXINO, 1980), além de outras variáveis observadas comumente em organismos dessa família (YOUBI et al, 2020).…”
Section: Chironomus Sancticaroliunclassified